Menstrual disorders and treatment seeking behaviour of adolescents - Rahatgaonkar, Veena G.; Wakankar, Anuradha H.; Oka, Gauri A.; Kamble, Sonal V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Menstrual abnormalities are a major gynaecological problem faced by adolescent girls leading to morbidity that may have an adverse effect on their school attendance. The objective of the study was to determine prevalence of menstrual disorders in girls aged 10-19 years and to study their treatment-seeking behaviour. Methods: We conducted a cross-sectional study on 592 girls in the age group of 10 to 19 years attending schools in Pune city during January 2016 to December 2016. Permission was sought from school authorities. Girls 10-17 years were included after obtaining parental consent. For 18 and 19 year olds, informed consent was taken from the girls themselves. Demographic information, height, weight and characteristics of menstrual period were noted. Results: Majority girls (36%) were in age group 12.1-14 years. Most prevalent menstrual disorder was painful menses reported by 70% of girls, followed by heavy menstrual bleeding (46%) and cycle irregularity (22%). All menstrual disorders were most commonly prevalent in the age group of 14.1 to 16 years. Proportion of girls visiting a doctor and taking medications for painful menses was 26.7% and 16.5% respectively, for heavy menstrual bleeding was 25.7% and 16.5% respectively and for cycle irregularity was 33% and 16.5% respectively. No association was found between mother’s education and treatment seeking behaviour for menstrual disorders. Conclusions: In spite of high prevalence of menstrual disorders, only a minority of the adolescents seek expert advice. This underscores the need for creating awareness among girls, mothers and teachers and developing a screening tool to identify girls who could benefit by further investigation and follow-up.